THE EVOLUTION OF CORPUS LINGUISTICS AND LANGUAGE TEACHING IN THE AGE OF ARTICICIAL INTELLIGENCE: FROM METODOLOGICAL PRECISION TO SOCIETAL IMPACT - Bazarbayeva Gulbanu Axmetovna (TILSHUNOSLIK VA CHET TILLARNI O‘QITISHDA ZAMONAVIY RAQAMLI TEXNOLOGIYALARDAN FOYDALANISH MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article examines the evolution of corpus linguistics and language teaching in the age of artificial intelligence, focusing on their methodological development and societal impact. The study analyzes how corpus-based approaches support data-driven language learning and how AI technologies influence modern educational practices through a qualitative review of relevant literature. The findings show that corpus linguistics provides reliable linguistic evidence, while artificial intelligence enhances accessibility and personalization in learning. However, the growing use of AI also raises concerns about accuracy and critical language awareness. Overall, both approaches can be effective when applied in a balanced way.